Surgical management of papillary thyroid carcinoma coexisting with Hashimoto’s disease: a single-center retrospective cohort study - Zhang, Dongdong; Wu, Jixiang; Chen, Lin (Frontiers in Endocrinology, 2024)
The mechanism and impact of Hashimoto's disease (HT) in patients with papillary thyroid carcinoma (PTC) remains a subject of ongoing debate. The optimal extent of thyroid resection is also controversial in cases of low-risk PTC.Objective: To investigate the clinical outcomes and prognoses associated with different extents of surgical resection in patients diagnosed with PTC coexisting with HT.We retrospectively analyzed data on the clinical features and treatment outcomes of patients with PTC concomitant with HT who underwent lobectomy with isthmusectomy and those who underwent total thyroidectomy at